Multi-morbidity and Highly Effective Contraception in Reproductive-Age Women in the US Intermountain West: a Retrospective Cohort Study - Gawron, Lori M. (J Gen Intern Med, 2019)
BACKGROUND: Women with chronic health conditions benefit from reproductive planning and access to highly effective contraception. OBJECTIVE: To determine the prevalence of and relationship between chronic health conditions and use of highly effective contraception among reproductive-age women. DESIGN: Retrospective cohort study using electronic health records. PARTICIPANTS: We identified all women 16–49 years who accessed care in the two largest health systems in the US Intermountain West between January 2010 and December 2014. MAIN MEASURES: We employed administrative codes to identify highly effective contraception and flag chronic health conditions listed in the US Medical Eligibility Criteria for Contraceptive Use (US MEC) and known to increase risk of adverse pregnancy outcomes. We described use of highly effective contraception by demographics and chronic conditions. We used multinomial logistic regression to relate demographic and disease status to contraceptive use. KEY RESULTS: Of 741,612 women assessed, 32.4% had at least one chronic health condition and 7.3% had two or more chronic conditions. Overall, 7.6% of women with a chronic health condition used highly effective contraception vs. 5.1% of women without a chronic condition. Women with chronic conditions were more likely to rely on public health insurance. The proportion of women using long-acting reversible contraception did not increase with chronic condition number (5.8% with 1 condition vs. 3.2% with 5 or more). In regression models adjusted for age, race, ethnicity, and payer, women with chronic conditions were more likely than those without chronic conditions to use highly effective contraception (aRR 1.4; 95% CI 1.4–1.5). Public insurance coverage was associated with both use of long-acting reversible contraception (aRR 2.2; 95% CI 2.1–2.3) and permanent contraception (aRR 2.9; 95% CI 2.7–3.1). CONCLUSIONS: Nearly a third of reproductive-age women in a regional health system have one or more chronic health condition. Public insurance increases the likelihood that women with a chronic health condition use highly effective contraception.